Analisis kedisiplinan siswa melalui sholat dhuha di MAN 3 Kediri - Miladi Muhammad, adi (Maliki Interdisciplinary Journal, 2024)
Education has a crucial role in shaping students' character, including discipline. This research aims to understand the implementation and impact of the Dhuha prayer habit in forming student discipline at MAN 3 Kediri. The research method used is qualitative with a descriptive approach to gain an in-depth understanding of the relationship between relevant variables. The results of the research show that the practice of Dhuha prayers at MAN 3 Kediri has helped students and girls develop discipline and improve their spiritual quality. The implementation of the Dhuha prayer is also seen to be related to the madrasah's vision and mission in forming Islamic character and a healthy environmental culture. Student discipline is an important aspect of education, and carrying out Dhuha prayers is one of the efforts to shape it. Support from teachers and parents is very important in this process. Therefore, character development in an educational environment is very important to achieve dignified educational goals.